Potential role of the heat shock protein 90 (hsp90) in buffering mutations to favour cyclical parthenogenesis in the peach potato aphid Myzus persicae (Aphididae, Hemiptera). Issue 4 (12th September 2018) - Mandrioli, M.; Zanetti, E.; Nardelli, A.; Manicardi, G.C.
Abstract: Heat-shock proteins 90 (hsp90s) are a class of molecules able to stabilize a network of 'client' proteins that are involved in several processes. Furthermore, recent studies indicated that mutations in the hsp90-encoding gene induce a wide range of phenotypic abnormalities, which have been interpreted as an increased sensitivity of different developmental pathways to hidden/cryptic mutations. In order to verify the role of hsp90 in aphids, we amplified and sequenced the hsp90 gene in 17 lineages of the peach potato aphid Myzus persicae (Sulzer, 1776) looking for the presence of mutations. In particular, we compared lineages with different reproductive modes (obligate vs. cyclical parthenogenesis), propensity to develop winged females and karyotype stability. Differently from the cyclical parthenogenetic lineages that possessed functional hsp90 genes, the seven analysed asexual lineages showed severe mutations (including frameshift and non-sense mutations). In vivo functional assays with the hsp90-inhibitor geldanamycin showed that some lineages with cyclical parthenogenesis may lose their ability to induce sexuales in the absence of active hsp90 revealing the presence of cryptic mutations in their genomes. As a whole, our data suggest that hsp90 could play in aphids a role in buffering hidden/cryptic mutations that disrupt cyclical parthenogenesis.